Implementasi Model Pembelajaran Inquiry Dalam Meningkatkan Pemahaman Mata Pelajaran PAI Di SMK 10 Nopember Jombang - Muhammad Asy’ari Hudaddin; Aida Arini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The research focuses on: (1) How the inquiry learning model is implemented at SMK 10 Nopember Jombang, (2) How students’ understanding of PAI subjects is developed, and (3) How the inquiry learning model is implemented to improve Islamic Religious Education (PAI) comprehension at SMK 10 Nopember Jombang. This study uses a descriptive qualitative method with a case study approach, relying on observation, interviews, and documentation as data collection techniques. The research findings indicate that: (1) Implementation of the Inquiry Learning Model at SMK 10 Nopember Jombang is carried The implementation of the inquiry learning model at SMK 10 Nopember Jombang was carried out in stages, passing through several important phases: initial reinforcement, topic identification, provision of stimuli, utilization of various learning resources, and the formation of working groups followed by discussions and presentations. In teaching and learning activities, the teacher functions as a facilitator and motivator for students' learning enthusiasm. (2) A significant increase in students' understanding of Islamic Religious Education (PAI) was observed. This was indicated by several factors, including increased focus and learning drive, better ability to respond to lesson content, courage to express opinions, and higher compliance in completing assignments and participating in learning activities. (3) The use of the inquiry learning model has proven effective in deepening students' understanding of PAI material. Learning became more interactive, students actively participated in the information-seeking process, and were able to construct their own understanding.